2020
DOI: 10.12669/pjms.36.3.1370
|View full text |Cite
|
Sign up to set email alerts
|

Stunting and associated factors in children of less than five years: A hospital-based study

Abstract: Objectives: To estimate frequency of stunting and associated factors in children aged less than five years in a tertiary care hospital of Lahore. Methods: An Analytical cross-sectional study was conducted in Pediatrics Outpatient Department at Akhtar Saeed Trust Teaching Hospital, Lahore from December 2017 to July 2018. Two hundred children of ages under five years coming to outdoor for treatment of minor ailments were included after informed consent from their parents. Non-probability, convenient sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 23 publications
1
10
0
6
Order By: Relevance
“…Families with low economic status have the opportunity of possibly suffering from malnutrition. This is in line with the previous research [16] that children from poor families are the most vulnerable. Increase in family members leads to decrease in food availability.…”
Section: The Relationship Between Birth and Birth Spacing With Stunting Eventssupporting
confidence: 93%
See 1 more Smart Citation
“…Families with low economic status have the opportunity of possibly suffering from malnutrition. This is in line with the previous research [16] that children from poor families are the most vulnerable. Increase in family members leads to decrease in food availability.…”
Section: The Relationship Between Birth and Birth Spacing With Stunting Eventssupporting
confidence: 93%
“…Inadequate dietary intake is one of the direct causes of malnutrition because it can cause weight loss or stunting growth. Therefore, the number of recorded births is a factor that also determines the nutritional status [16]. Results also showed that the relationship between the number of children and nutritional status caused competition in facilities and infrastructure, food differences, and reduced care time, causing stunting.…”
Section: The Relationship Between Birth and Birth Spacing With Stunting Eventsmentioning
confidence: 99%
“…Therefore stunting may be caused by several other factors that influence the incidence of stunting in the region. These factors include an unhealthy physical environment such as not available hygiene water and poor sanitation [17] [18], which have an impact on the risk of diarrheal diseases and other infectious diseases, causing children to have difficulty eating [13][19], children who are picky eaters [20][21] [22] and a less supportive social environment has an impact on the diet of stunted children under five [9][23] [24] such as parental diet models [25], maternal knowledge [26][27], unsafe food for consumption [28].…”
Section: Resultsmentioning
confidence: 99%
“…In developing countries, one study in Malaysia reported that the prevalence of acute and chronic under-nutrition among hospitalized children were 11% and 14% respectively [22]. In Pakistan the prevalence of stunting among children attending out-patient clinics was 21% [23]. In one controversial result from Tanzania; the prevalence of stunting and wasting was 8.37% & 1.41% respectively among children attending hospitals and primary care centers with predominance of boys' malnutrition over females [24].…”
Section: The Socio-economic Characteristics and Malnutritionmentioning
confidence: 99%